Auriferous Paleozoic Accretionary Terranes Within the Mongol - Okhotsk Suture Zone, Russian Far East - A C. Edwards (The Australasian Institute of Mining and Metallurgy, 1999)
The Mongol-Okhotsk belt consists of detached fragments of the Circum Pacific fold belt which have been trapped within the Mongol-Okhotsk fold belt. In its western part, the structures of the belt form an east-facing loop that is not connected with the other orogenic structures of Central Asia. In the eastern part of the belt (the Mongol-Okhotsk suture zone) the terranes form a zone between the Siberian craton to the north and the Bureya composite terrane to the south, that is linked with the Circum Pacific belt. The accretionary terranes, together with their Precambrian backstops, form a series of consistently-stacked, paired units that are bounded by northwest and north trending sinistral strike-slip faults. The ages of the rocks forming these accretionary complexes vary from Late Precambrian - Carboniferous in the west to Cambrian - Jurassic in the east. The terranes developed due to a progressive westward stacking of the accretionary complexes during the process of accretionary growth. The magmatic rocks young eastward indicating that migration of the magmatic front of the arc followed the eastward growth of the accretionary complexes. The accretionary terranes may be differentiated by their Paleozoic lithological assemblages. Only the Selemdzha, Niman, and Kerbi terranes located in the eastern part of the Mongol-Okhotsk suture zone contain significant amounts of black shale, and it is these terranes that host the bulk of the hardrock and placer gold mineralisation that is present within the suture zone. Gold mineralisation is present both as vein style and disseminated mineralisation within structural duplexes.